2017
DOI: 10.1002/ece3.2940
|View full text |Cite
|
Sign up to set email alerts
|

Population size, center–periphery, and seed dispersers’ effects on the genetic diversity and population structure of the Mediterranean relict shrub Cneorum tricoccon

Abstract: The effect of population size on population genetic diversity and structure has rarely been studied jointly with other factors such as the position of a population within the species’ distribution range or the presence of mutualistic partners influencing dispersal. Understanding these determining factors for genetic variation is critical for conservation of relict plants that are generally suffering from genetic deterioration. Working with 16 populations of the vulnerable relict shrub Cneorum tricoccon through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 85 publications
(133 reference statements)
0
9
1
Order By: Relevance
“…It is worth noting that the He found in this study is significantly higher than that found in some narrowranging species (He = 0.420) and in some widely distributed species (He = 0.620) [55]. Studies have shown that genetic diversity is positively correlated with population size [56][57][58]. Surprisingly, in this study, neither Ho (P = 0.953) nor He (P = 0.166) was significantly related to the population size (Figure 1).…”
Section: High Level Of Genetic Diversitycontrasting
confidence: 62%
“…It is worth noting that the He found in this study is significantly higher than that found in some narrowranging species (He = 0.420) and in some widely distributed species (He = 0.620) [55]. Studies have shown that genetic diversity is positively correlated with population size [56][57][58]. Surprisingly, in this study, neither Ho (P = 0.953) nor He (P = 0.166) was significantly related to the population size (Figure 1).…”
Section: High Level Of Genetic Diversitycontrasting
confidence: 62%
“…; Lázaro‐Nogal et al. ). It produces fleshy fruits consisting of three or (more rarely) four cocci (locules of a syncarpous ovary; Fig.…”
Section: Methodsmentioning
confidence: 97%
“…The species is considered a relict of the Mediterranean flora that evolved during the early Tertiary (Traveset et al 2012 and references therein). It inhabits southeastern Spain, southeastern France, and western Italy (Sardinia, Giannutri and Tuscany), with the main populations in the Balearic Islands (Traveset et al 2012;Lázaro-Nogal et al 2017). It produces fleshy fruits consisting of three or (more rarely) four cocci (locules of a syncarpous ovary; Fig.…”
Section: Study Systemmentioning
confidence: 99%
“…Nevertheless, there is evidence of the effects of connectivity on the fitness of gypsophile species, showing the importance of including habitat connectivity in management and conservation strategies for G . bermejoi , and other species and communities associated with specialist soils [75] .…”
Section: - Discussionmentioning
confidence: 99%